Protection of the Right to Freedom of Religion in Indonesia (Case Study: Destruction of the Ahmadiyah Mosque in Balai Harapan Village, Temunak District, Sintang District, West Kalimantan) (Universitas Negeri Semarang, 2021)
As in most modern law countries, the State of Indonesia has a regulation regarding guarantees for religious rights and freedoms. This is implied in the constitution of the State of Indonesia, namely the 1945 Constitution of the Republic of Indonesia, precisely in Article 28 E paragraph (1) which reads